2014
DOI: 10.6061/clinics/2014(09)05
|View full text |Cite
|
Sign up to set email alerts
|

An evaluation of the professional, social and demographic profile and quality of life of physicians working at the Prehospital Emergency Medical System (SAMU) in Brazil

Abstract: OBJECTIVE:To describe the profile of physicians working at the Prehospital Emergency Medical System (SAMU) in Brazil and to evaluate their quality of life.METHODS:Both a semi-structured questionnaire with 57 questions and the SF-36 questionnaire were sent to research departments within SAMU in the Brazilian state capitals, the Federal District and inland towns in Brazil.RESULTS:Of a total of 902 physicians, including 644 (71.4%) males, 533 (59.1%) were between 30 and 45 years of age and 562 (62.4%) worked in a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 30 publications
0
12
0
1
Order By: Relevance
“…7 Also physiologic scores, such as RTS have limitations because normal heart and respiratory rates in children are much higher than in adults 26 .…”
Section: ■ Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…7 Also physiologic scores, such as RTS have limitations because normal heart and respiratory rates in children are much higher than in adults 26 .…”
Section: ■ Discussionmentioning
confidence: 99%
“…A study of medical pre-hospital system in Brazil showed that 51.5% of physicians feel unprepared to meet traumatized children; 34.9% have difficulties in pediatric semiology and 62.4% have difficulty pediatric advanced life support procedures 7 .…”
Section: ■ Introductionmentioning
confidence: 99%
“…They maintain a broad range of practice and are able to perform many emergent procedures that are above the scope of practice of a paramedic in the United States, such as pericardiocentesis, surgical airway, thoracocentesis, and central line access. A recent study indicates that only a small percentage of physicians working with SAMU have completed SAMU-specific or advanced prehospital training and many feel uncomfortable with the prehospital environment in the areas of pediatric trauma and surgical procedures (Tallo 2014). All physicians that we interviewed completed Advanced Trauma Life Support training and all prehospital care providers, including nurses and drivers, have completed PreHospital Trauma Life Support (PHTLS) training [19].…”
Section: Population and Settingmentioning
confidence: 99%
“…A recent study indicates that only a small percentage of physicians working with SAMU have completed SAMU-specific or advanced prehospital training and many feel uncomfortable with the prehospital environment in the areas of pediatric trauma and surgical procedures (Tallo 2014). All physicians that we interviewed completed Advanced Trauma Life Support training and all prehospital care providers, including nurses and drivers, have completed PreHospital Trauma Life Support (PHTLS) training [19]. The BLS unit consists only of a driver and nurse technician.…”
Section: Population and Settingmentioning
confidence: 99%
“…The underfunding of this public system, the high cost of advances in medicine, the difficulty of retaining health professionals in small and distant towns, and the abandonment of hospitals and health facilities, often due to the diversion of resources in a country contaminated by corruption, all mean that health care provision is a serious problem in our midst. This is most evident in the area of emergencies, with overcrowded first aid centers, few diagnostic and therapeutic resources, lack of inpatient beds, inadequately trained medical teams, for both pre-hospital and in-hospital care, among many others problems 2 .…”
mentioning
confidence: 99%